The prevalence, incidence, and persistence of self-reported visual impairment among Chinese population with diabetes mellitus: evaluation from a nationally representative survey, 2015–2018 - Zhou, Yifan; Wei, Jin; Wang, Ning; Chen, Yisheng; Fang, Cheng; Zhou, Minwen; Zhou, Xinrong; Luo, Jianfeng; Wang, Xiaodong; Peng, Qing (Frontiers in Public Health, 2023)
Aims: To investigate the prevalence, incidence, persistence of vision impairment and their correlates among Chinese population with diabetes over 3 years. Materials and Methods: The China Health and Retirement Longitudinal Survey is the first nationally representative longitudinal survey in Chinese population. Cross-sectional analysis of prevalent vision impairment in 2015 included 2173 diabetic participants. Longitudinal observation of incident and persistent vision impairment included 1633 participants from 2015 to 2018. Risk factors of vision impairment were identified by univariate and multivariate logistic regression analyses. Results: Among our population with diabetes, 11.79% reported vision impairment in 2015, 4.51% had persistent vision impairment to 2018, and 8.90% developed vision impairment in 2018. Factors including increased age, female gender, less educational attainment, living in rural area, medication or non-medication treatment, diabetes tests, use of eye glasses and poorer health status were correlated to vision impairment (all p＜0.05). Conclusions: Based on the most recently available national data, we provide a baseline for future public health initiatives on visual impairment among Chinese population with diabetes. Multiple risk factors were identified as references to diverse public health strategies and interventions to reduce the burden of vision impairment among diabetic population in China.